2000
DOI: 10.3184/095422900782775481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic acids on the availability of cadmium in wheat

Abstract: Pot experiments were conducted to investigate the effect of various organic (carboxylic and amino) acids on the uptake and translocation of root-absorbed cadmium by wheat (Triticum vulgare) plants grown in sand and soil culture. Statistically significant increases in cadmium accumulation from cadmium treated plants in the presence of increasing concentration of organic acids suggest the existence of Cd-organic acid interactions in the soilplant system resulting into the formation of organically bound cadmium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…The effects of root exudates on element mobility and pH level in soil is presented as depletion curves in Figures 1-4. Although the excretion of root exudates obviously lead to decreasing pH (Nigam et al 2000, Loosemore et al 2004, in our experiment soil pH in control sample decreased from 6.1 to 5.5 with increasing distance from the roots. Schoettelndreier and FalkengrenGrerup (1999) presented increasing rhizosphere pH compared to bulk soil where the increase correlated with the uptake of NO 3 -by the plants.…”
Section: Rhizobox Experimentscontrasting
confidence: 67%
See 1 more Smart Citation
“…The effects of root exudates on element mobility and pH level in soil is presented as depletion curves in Figures 1-4. Although the excretion of root exudates obviously lead to decreasing pH (Nigam et al 2000, Loosemore et al 2004, in our experiment soil pH in control sample decreased from 6.1 to 5.5 with increasing distance from the roots. Schoettelndreier and FalkengrenGrerup (1999) presented increasing rhizosphere pH compared to bulk soil where the increase correlated with the uptake of NO 3 -by the plants.…”
Section: Rhizobox Experimentscontrasting
confidence: 67%
“…Statistically significant increases in cadmium accumulation of wheat plants grown on cadmium treated soils in the presence of increasing concentration of organic acids suggest the existence of Cd-organic acid interactions in the soil-plant system resulting into the formation of organically bound cadmium which is mobile and plant available (Nigam et al 2000). Concentration of carboxylic acids and their composition in soil solution depends also on element and its concentration level.…”
mentioning
confidence: 99%
“…Cieśliń ski et al (1998) found that the high Cd accumulating durum wheat cultivar Kyle had significantly higher amounts of organic acids in the rhizosphere soil than that of the low accumulating cultivar Arcola, regardless of soil type. Statistically significant increases were observed in Cd accumulation by wheat with increasing concentrations of organic acids in pot experiments (Nigam et al, 2000). Under hydroponic conditions, Cd uptake and translocation in tomato plants increased after citric acid preincubation (Senden et al, 1995).…”
Section: Introductionmentioning
confidence: 90%
“…Root exudates include both high-and lowmolecular-weight compounds, and among them organic acids are some that are likely to affect release and availability of metals in the soil. Cieslinski et al (1997) found that the release of organic acids was cultivar dependent and Nigam et al (2000) demonstrated that organic acids from wheat increased the release of Cd from soil. Cieslinski et al (1998) suggested that different organic acid compositions played an important role in determining the capacity to accumulate Cd in different cultivars of durum wheat.…”
Section: Introductionmentioning
confidence: 98%